Hubungan Motivasi Intrinsik dan Ekstrinsik terhadap Keberhasilan Pembelajaran Orang Dewasa : Systematic Literature Review dan Analisis Bibliometrik - Naila Ula; Mela Amelia; Anggi Fitriani; Nurlaela Hamidah (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the relationship between intrinsic and extrinsic motivation and adult learning success through a Systematic Literature Review (SLR) using the PRISMA framework. A search on Google Scholar (2024–2026) yielded 19 articles that met the inclusion criteria; these were analyzed using narrative-thematic and bibliometric methods with VOSviewer. The results indicate that intrinsic motivation is more strongly associated with persistence, deep engagement, and long-term learning transfer, whereas extrinsic motivation acts as an initial catalyst, particularly in professional and institutional contexts. Both types of motivation are complementary through internalization mediated by self-efficacy, social support, and adaptive learning design. Contextual factors (stage of adulthood, culture, digital environment) also moderate these relationships. Educators and program designers need to integrate flexible and context-specific motivational strategies.